PERAN PRAKTEK CORPORATE GOVERNANCE SEBAGAI MODERATING VARIABLE DARI PENGARUH EARNINGS MANAGEMENT TERHADAP NILAI PERUSAHAAN - TANYAWATI, . (Berkala Ilmiah Mahasiswa Akuntansi)
A go public companies get their source of founding from shares selling at stock market. Therefore, manager always tries to give finance information that shows the maximum profit so the company’s value could get higher. This condition will motivate manager to do earnings management. One of way that could be used to restrict earnings management is corporate governance. The purpose of this research is to see if the corporate governance could give effect to the relation between earning management and company’s value. The object of this research is a go public banking companies that listed on the Stock Exchange in 2007-2010. Data analysis techniques that used on this research is multiple linear regressions. The result of this research is showing that managerial ownership doesn’t make effect the relation between earnings management and company’s value. On the other hand, institutional ownership, audit quality and independent commissioner make a significant effect to the relation between earnings management and company’s value.